Efficacy of Nasya Karma and Trayodashanga Guggulu for the Management of Avabahuka (Frozen Shoulder) - Rani, Tinkle; Singh, Vidhi; Wetal, Vishakha Rajesh; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2022)
Background: Avabahuka (Frozen Shoulder) is one of the type of musculoskeletal disability primarily affecting the middle aged to older persons as a degenerative and neurological condition with symptoms being pain and disability. Modern approaches comes with wide range of modalities such as analgesics, muscle relaxants, steroids, physiotherapy, and even operative procedures but none of them gives satisfactory and permanent results. Aim: To study the efficacy of Mahamasha Taila Nasya with Trayodashanga Guggulu in comparison to only administration of Trayodashanga Guggulu in Avabahuka. Materials and Methods: This study was conducted on 36 clinically diagnosed cases of Avabahuka from OPD of Ch. Brahm Prakash Ayurved Charak Sansthan, Khera Dabar, Najafgarh, New Delhi in a period of 18 months after taking institutional ethical clearance. Parameters to evaluate the analgesic effect were SPADI Score, Assessment of Bahupraspandanhara and Assessment of Ansa Shoola. Participants were divided into two groups: Group A – Mahamasha Taila Nasya Karma with Trayodashang Guggulu and in Group B- Tryodashanga Guggulu was given. Results: Both the groups were found equivalently significant when compared statistically with the difference found between two groups as- in Group A there was a relief of 63.41% in Bahupraspandanhara, Ansa shool- 71.05% and SPADI Score – 30.86% whereas in Group B there was a relief of 60.98% in Bahupraspandanhara, Ansa shool- 61.54% and SPADI Score – 29.57%. Clinically, Group A was found better than Group B. Conclusion: Both the groups showed mild to moderate relief in the management of Avabahuka. No major adverse or side effects were encountered during the course of study